Urgensi Ulumul Qur`an Dalam Menajaga Otentisitas Al-Quran - Ridwan Noorwahid Mohtar; Abdul Azis; Yazied Mauvi Nazier; Tegar Pria Utama; Azkya Raudi Ardillah; Akhmad Dasuki (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Ulumul Qur’an is a scientific discipline that plays a crucial role in preserving the authenticity of the Qur’an, both in terms of text and meaning. Amid the growing trend of instant interpretations of the Qur’an that lack a solid methodological foundation, the role of Ulumul Qur’an has become increasingly urgent. This article aims to examine the importance of Ulumul Qur’an in safeguarding the authenticity of the Qur’an and its relevance in addressing contemporary interpretative challenges. This study employs a library research method with a descriptive-analytical approach to classical and contemporary works on Ulumul Qur’an. The findings indicate that Ulumul Qur’an serves as a methodological foundation for Qur’anic interpretation and as an academic filter to prevent distortion of the divine message. Therefore, strengthening the study of Ulumul Qur’an is an essential necessity to maintain an authentic and responsible understanding of the Qur’an.